Do Brazilian Banks Compete? - Belaisch, Agnes (IMF Working Papers; Working Paper ;, 2003)
More developed financial systems are associated with higher investment and better economic performance. This paper discusses possible factors that may inhibit a deepening of bank intermediation and more efficient banking in Brazil, two aspects that are found to be significantly different than in leading banking systems in other parts of the world. Using panel data, it finds positive evidence of the presence of a noncompetitive market structure in the Brazilian banking system, a factor that could explain why intermediation may be relatively low and costly. When banks behave like local monopolies or oligopolies, incentives to improve efficiency are weak and the interest rate spread is large, discouraging higher lending volumes.